Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing pada UMKM Konveksi di Nganjuk - Nabila Intan Pramesti; Diah Anugrah Sharasanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research was conducted with the aim of analyzing and evaluating the calculation of the cost of goods manufactured using the job order costing method in the convection industry in Nganjuk. The background of this research is that so far, convection MSMEs have calculated the Cost of Goods Sold in a simple way, namely by adding the purchase of raw materials (direct materials) with direct labor costs and factory overhead costs (indirect materials) of 10% of the total sum of raw materials and labor wages. Data collection techniques used include direct observation, interviews, and analysis of transaction evidence. Data analysis was carried out with a descriptive approach, namely describing the facts of the calculation of COGS that have been carried out by convection MSMEs, then a more in-depth analysis was carried out. In the production process of 240 shirts, 480 pants, and 13 vests, the cost of goods manufactured by the company was Rp. 124,713 per shirt, Rp. 115,617 per pants, and Rp. 102,105 per vest, respectively. Meanwhile, the cost of goods manufactured using the job order costing method is Rp. 143,456 per shirt, Rp. 119,346 per pair of trousers, and Rp. 146,123 per vest. This difference arises because the garment SME applies a 10% rate of raw material costs and direct labor costs in calculating factory overhead costs, while in the job order costing method, production costs that directly affect the product are calculated in more detail.